2022
DOI: 10.1371/journal.pone.0271974
|View full text |Cite
|
Sign up to set email alerts
|

Observed trends and projections of temperature and precipitation in the Olifants River Catchment in South Africa

Abstract: Among the projected effects of climate change, water resources are at the center of the matrix. Certainly, the southern African climate is changing, consequently, localized studies are needed to determine the magnitude of anticipated changes for effective adaptation. Utilizing historical observation data over the Olifants River Catchment, we examined trends in temperature and rainfall for the period 1976–2019. In addition, future climate change projections under the RCP 4.5 and RCP 8.5 scenarios for two time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Recent studies warn that, in this state, 1980-2019 air temperatures have increased by about 0.01 • C per year (0.008-0.017 • C) [26]. Similar annual change magnitudes have also been detected in South Africa or Australia [27][28][29]. However, the region of the globe where the Mediterranean climate reaches its maximum extent is in the European Mediterranean Basin [22].…”
Section: Introductionmentioning
confidence: 69%
“…Recent studies warn that, in this state, 1980-2019 air temperatures have increased by about 0.01 • C per year (0.008-0.017 • C) [26]. Similar annual change magnitudes have also been detected in South Africa or Australia [27][28][29]. However, the region of the globe where the Mediterranean climate reaches its maximum extent is in the European Mediterranean Basin [22].…”
Section: Introductionmentioning
confidence: 69%
“…According to the IPCC (2007) [1], the temperature in Africa is predicted to increase by 1.5 to 3 • C by 2050. Malhi and Wright (2004) [2] discovered that African tropical forests and South Africa will get warmer by 0.29 • C. Adeola et al (2022) [3], using a modified Mann-Kendall test on historical observation data from the period 1976-2019, found that the Olifants River Catchment in South Africa experienced an increase in temperature and an overall decline in rainfall, although no significant changes were detected in the distribution of rainfall time. Hulme et al (2005) [4] stated that rainfall in Africa has both spatial and temporal variability: in West Africa since the late 1960s, rainfall has been decreasing (Nicholson and Selato, 2000;Chappell and Agnew 2004;Dai et al, 2004) [5][6][7] while the Guinean coast recorded a 10% increase in annual rainfall between 1995 and 2005.…”
Section: Introductionmentioning
confidence: 99%